Uncovering the origins of supramolecular similarity in a series of benzimidazole structures. Issue 37 (12th September 2022) - Orlando, Tainára; Lopes, Leandro C.; Neumann, Darlon A. M.; Andrade, Valquiria P.; Mittersteiner, Mateus; Rocha, Cláudia Q.; Zanatta, Nilo; Bonacorso, Helio G.; Martins, Marcos A. P.; Salbego, Paulo R. S.
Abstract : Quantitative similarity indices ( I X ) were combined with crystallization mechanism proposals to shed more light on the origins of the supramolecular similarity between a series of benzimidazole derivative structures. Abstract : This study sought to propose the origins of the supramolecular similarity between a series of benzimidazole derivatives structures, and our findings indicated that it occurs due to the approximation of the initially formed one-dimensional nuclei during crystallization. Supramolecular comparisons were carried out by calculating the quantitative similarity indices I X (X = D, C, or G) based on geometric ( I D ), contact area ( I C ), and stabilization energy ( I G ) parameters. The similarity indices were successfully used as tools to quantify and classify the different regions of supramolecular similarity between the crystal structures. The multiparameter index I DCG demonstrated distinct similarity regions in the supramolecular comparisons. All structures with substituents (2–5 ) presented a high similarity when compared amongst each other; the unsubstituted compound 1 was the only with a low similarity after being compared to the rest of the series. Hence, we proposed that the formation of one-dimensional nuclei assisted by hydrogen bond interactions interspersed with π⋯π interactions occurs in the first stage of crystallization, showing the dominance of the energetic parameter. After this, these one-dimensional nuclei presented a pattern of approximation and complementarity similar to compounds 2–5, leading to crystal lattices with a high supramolecular similarity degree between these compounds. Nevertheless, compound 1 favored a distinct complementarity between the one-dimensional nuclei, giving rise to a crystal lattice distinct from compounds 2–5 . These findings emphasize that isostructurality must be seen as a broad concept whilst considering a supramolecular perspective using distinct quantitative parameters to perform comparable classifications in regions of similarity.